STRATEGI PENGEMBANGAN SUMBER DAYA MANUSIA DALAM MANAJEMEN PENDIDIKAN ISLAM DI ERA DIGITAL - Habib , Habib; Haris , Irham Abdul; Muslihun , Muslihun; Wawan, Ade (Sekolah Tinggi Ilmu Syrari’ah Daru ‘Ulum (STSDU) Lampung Timur., 2023)
This study aims to investigate the development of learning strategies that are in accordance with the learning paradigm in the digital era in the context of Islamic education. The focus of this research is to integrate the use of technology with Islamic values in Islamic education. The research method used is qualitative research involving students, teachers, and related human resources. The results of the study show that the integration of technology in Islamic education can increase interactivity, student involvement, and accessibility to learning resources. The use of online learning platforms, educational applications, and other digital resources provides opportunities to enrich student learning experiences. However, it is also important to ensure that the use of this technology remains in line with Islamic values. Therefore, learning strategies that integrate Islamic values with the use of technology are very important to maintain conformity with religious teachings. In addition, this research shows that the learning paradigm in the digital era encourages collaboration and independent learning. Learning strategies that involve group work, online discussions, and collaborative projects can increase student engagement and build their social competence. Providing opportunities for independent learning by utilizing digital resources can also strengthen students' independence in acquiring knowledge. Formative evaluation and effective feedback are also an important part of developing learning strategies in the digital era. Through online learning platforms, teachers can provide real-time feedback and identify student needs in a more timely manner. This helps improve student understanding and performance. Finally, this study emphasizes the importance of developing human resource professionalism in education management. Human resources need to attend relevant training and development to acquire the knowledge and skills needed to integrate technology with Islamic education. In order to maximize the benefits of using technology in Islamic education, there is a need for continuous efforts to develop relevant learning strategies, ensure the integration of Islamic values, and strengthen HR competencies in education management. Thus, Islamic education can develop according to technological developments and prepare students well to face challenges in the digital era